Using Social Media as Tools of Health Protocol Campaign in the Era of the Covid-19 Pandemic in Indonesia - Dimas Subekti; Suranto (International Journal of Media and Communication Research, 2021)
The entry of Covid-19 in Indonesia prompted the Indonesian government to make policies to tackle the virus's spread. The approach adopted by the Indonesian government is large-scale social restrictions (PSBB). The problem is that there are still violations of health protocols that have created a new Covid-19 cluster amid society. Therefore, this study aims to find out more about the use of social media for health protocol campaigns in the era of the Covid-19 pandemic in Indonesia. This study uses Q-DAS (Qualitative Data Analysis Software) with Nvivo 12 plus for data analysis. This study uses three different analyzes, chart analysis, cluster analysis, and word cloud analysis. This study uses trending hashtags on Twitter social media relevant to the health protocol campaign in the era of the Covid-19 pandemic. The results of this study are first, Twitter social media is one of the places to campaign for health protocols in the era of the Covid-19 pandemic. Second, the "physical distancing" health protocol campaign is dominant in #SocialDistancing, "using a mask" is prevalent in #jagajarak, and "handwashing" is often used in #lawancovid19 and #jagajarak. Third, several hashtags used in social media Twitter about health protocols are interconnected, but the most powerful are #pakaimasker with #jagajarak. Fourth, the word that is most popular and which is often discussed concerning health protocols on Twitter is #SocialDistancing.